Investment in Community Development and Return on Assets: Does it Matter? - C. G, Ahannaya; A. T, Iwala; J. E, Umukoro (International Journal of Business Strategy and Social Sciences, 2021)
The debate as to what drives return on asserts has remained unabated. Contextual reports have shown that despite organizations declaring several corporate responsibility initiatives to collaborate with the host communities, financial pointers of Oil firms such as, return on assets have maintained fluctuating performance and a steady decline. Thus, this paper probed into the impact investment in community development has on return on assets. The paper employed an Ex-post facto research design with a focus on the population of five multinational oil firms in Nigeria based on availability of data. The study made use of secondary data sourced from the annual reports of the sampled oil companies for a period of ten years (2006 - 2015). The study adopted inferential statistics for panel data analysis. Results revealed that investment in community development had a positive significant impact on ROA (R2 = 0.44, t-statistic is -3.486992 and p = 0.0011) of multinational oil companies in the Niger Delta Nigeria. The study recommended that management of companies should adopt viable strategies to explore community development for the host communities and improve companies host communities’ liaison to achieve sustainable development and guarantee enabling business operating environment in return.